Diseño e implementación de un dispositivo, que permita mejorar la cobertura para tarjetas RFID activo. - Cargua Quishpi, Jhon Jairo (2017)
The use of technologies that facilitate the information transfer and a wireless network have a huge demand nowadays. This technology facilitates and simplify the processes in industries, businesses, hospitals and institutions. Due to this the main objective of this research is the implementation and design of a prototype in exchange for improving the radiant system and to get a better transmission range. An antenna array, microstrip, Harping filters and power splitters of Wilkinson for distribution of patches were used in order to improve the transmission range of the RFID reader that works in the 2.4GHz band, thusly this device will have a larger signal range for reading the tags. To achieve this objective an array of microstrip antennas was designed, each patch has a gain of 24.5dbm, moreover the design of the power splitter and the filter was designed by Ansys HFSS and AWR software. The Omni-directional active RFID reader model 240G 4 is controlled by a program provided by the company DweRF in China, R232 communication protocol is used for communication. The tests were performed at the laboratory and Colosseum of the National University of Chimborazo exposing the designed radiant system data link simulator; analyzed by ReaderDemo software in favor of getting data from the tag at different areas, besides using the spectrum analyzer tests were performed in order to get the values of system power radiant designed.